Kinetic and kinematic characteristics of setting motions in female volleyball players - Cabarkapa, D. V.; Cabarkapa, D.; Fry, A. C.; Whiting, S. M.; Downey, G. G. (Biomechanics, 2022)
While being an integral part of both the offensive and defensive segments of the game, the biomechanical parameters of setting motions remain understudied in the scientific literature. Thus, the purpose of the present study was to examine differences in kinetic and kinematic characteristics between: (a) three types of setting motions (i.e., front, middle, back); (b) two types of setting approaches (i.e., stationary, step-in); and (c) proficient (PRO) and non-proficient (N-PRO) volleyball players. Twenty recreationally active females performed five stationary and five step-in setting approaches to Zone 4-2 in a randomized order. Uni-dimensional force plate sampling at 1000 Hz and high-definition camera recording at 30 fps were used to obtain kinetic and kinematic variables of interest. The total number of setting attempts performed by each subject was 30, accounting for a grand total of 600 attempts. PRO setters had less knee flexion, shoulder flexion, and ankle dorsiflexion at the initial concentric phase of the volleyball setting motion when compared to the N-PRO setters. Moreover, significantly greater peak concentric and landing forces, impulse, rate of force development, and vertical jump height were observed for PRO setters compared to N-PRO setters, while no significant differences were found between different setting targets and approaches.